2011
DOI: 10.1590/s1984-70332011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in populations of sweet corn, common corn and teosinte

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Zea mays ssp. mexicana L. is a member of teosintes and a close wild relative of cultivated maize (Almeida et al, 2011 ). Although teosintes have not yet been widely used in maize breeding, the high genetic diversity shows that Zea mays ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Zea mays ssp. mexicana L. is a member of teosintes and a close wild relative of cultivated maize (Almeida et al, 2011 ). Although teosintes have not yet been widely used in maize breeding, the high genetic diversity shows that Zea mays ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, sweet corn production improvements in Brazil have consisted of obtaining hybrids (Kwiatkowski et al, 2011) and assessing diverse germplasm (Almeida et al, 2011;Terra et al, 2011) to form a broad genetic basis for local farmers. Information about genetic diversity in corn is essential to germplasm characterization and utilization (Gerdes and Tracy, 1994;Kashiani et al, 2012;Liu et al, 2003;Nigussie and Saleh, 2007;Revilla et al, 2005;Srdić et al, 2011;Tracy et al, 2000;Yousef and Juvik, 2001), particularly among the sul germplasm from southern Brazil (Amorin et al, 2003;Barbosa-Neto et al, 2005;Bered et al, 2005;Rupp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of molecular markers have been used to estimate genetic variability; these markers indicate the similarity between cultivars based on a direct analysis of the genome (Almeida et al, 2011). Simple sequence repeats of genomic DNA (SSRs, also known as microsatellite loci) have been considered adequate for estimating the genetic variability in sweet corn (Rupp et al, 2009).…”
mentioning
confidence: 99%
“…Similar results were also found by Lopes, Scapim, Mangolin, and Machado (2014), using 15 sweet corn inbred lines in a divergence genetic study, where they found 15 out of 100 polymorphic SSR markers had an average PIC of 0.41. Almeida, Amorim, Neto, Filho, and Sereno (2011) obtained PIC values ranging from 0.26 to 0.76 in populations of field corn and teosinte, while Nikolić et al (2019) found, in their genetic divergence study using 24 maize genotypes, PIC values ranging from 0.57 to 0.89 with an average value of 0.73. In addition, Cruz et al (2011) highlighted that PIC values reflect whether a marker is informative or not relative to their capacity for genetic divergence analysis.…”
Section: Resultsmentioning
confidence: 96%